Participation, Housing, and the Question of ‘Good Architecture’ - Maroš Krivý (Footprint)
The Tallinn Architecture Biennale ʻRecycling Socialismʼ, held in September 2013, is reviewed in this paper. Key themes and contradictions that crystallised throughout the event are identified and analysed. Participatory approach and its shortcomings are discussed in relation to the Biennaleʼs vision competition winning entry.